MENINGKATKAN MOTIVASI DAN KETERAMPILAN PEMBACAAN ALAT UKUR PADA MATA PELAJARAN MENGGUNAKAN ALAT UKUR DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DAN QUANTUM TEACHING - Sulistyo J Hartono (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study implements classroom action research to increase motivation and skills to apply readability of measurement tool kit, using contextual and quantum teaching.  The study used classroom action research method. The process of the research subsequently includes planning, action, observation and reflection. The observation includes notifications, recording and interview. The result of this research reveals that the student obtained improved competence in the end of the second cycle. All of the student passed the examination with score above 80 (A) and 80% student handed these competency